Direct and Indirect Speech Acts in Literary Works as Language Learning Media - Fikry Syahputra; Nurlela Nurlela; Icha Mawarni Br Ginting; Yuri Widiantho (Talenta Publisher, 2023)
This paper described the types and function of direct and indirect speech acts found in the novel On the Far Side of the Mountain by Jean Craighead George. Several theories, including Yule, Stewart, Vaillette, and Akmajian were utilized to analyze the utterances of the novel's characters. This paper was written using a descriptive qualitative methodology. The utterances spoken in the novel On the Far Side of the Mountain is the source of the data examined in this article. According to the analysis results, the novel On the Far Side of the Mountain utilized both direct and indirect speech acts when performing the dialogue. The direct speech acts were divided into five categories: direct speech acts in declarative sentences Type as an Assertion (435 utterances), direct speech acts in Imperative sentences Type as a Request (127 utterances), direct speech acts in Interrogative Type as a question (167 utterances), direct speech acts in Declarative Type as a Threat (5 utterances), and direct speech acts in Declarative sentences Type as a Promise (2 utterances). Meanwhile, indirect speech acts are in Declarative Type as an Assertion (2 utterances), indirect speech acts are in Declarative sentences Type as a Request (20 utterances) and Indirect speech acts are in Declarative sentences Type as a question (9 utterances). Direct speech acts in imperative sentence type as a request is the most dominant speech acts found in the novel.